ANALYSIS OF THE DEVELOPMENT AND FINANCIAL CONDITION OF ENTERPRISES DURING THE WAR PERIOD - L.V. (Економіка, управління та адміністрування, 2023)
In 2022, at least 109 large and medium-sized enterprises suffered direct losses as a result of the full-scale Russian invasion on February 24, 2022. The total amount of direct losses of enterprises, including state owners and entrepreneurs, is estimated at 1 13 billion, of which $9 billion is the share of losses of large and medium - sized enterprises.